2013
DOI: 10.1093/pcp/pct059
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Three BOR1 Genes Corresponding to Different Genomes in Response to Boron Conditions in Hexaploid Wheat (Triticum aestivum L.)

Abstract: Boron (B) is an essential micronutrient for plants. Efflux-type B transporters, BORs, have been identified in Arabidopsis thaliana and rice. Here we identified BOR1 genes encoding B efflux transporters, from the hexaploid genome of wheat (Triticum aestivum L.). We cloned three genes closely related to OsBOR1 and named them TaBOR1.1, TaBOR1.2 and TaBOR1.3. All three TaBOR1s showed B efflux activities when expressed in tobacco BY-2 cells. TaBOR1-green fluorescent protein (GFP) fusion proteins were expressed in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Among BOR genes in plants, TaBOR1.2 in wheat is reported to be induced under toxic levels of B supply (Leaungthitikanchana et al 2013), although the physiological function of TaBOR1.2 is still unclear. It has been also reported that transcript levels of a homologous gene to BOR (Bot1) is induced by high-B treatment in shoots of Puccinellia distans, an extremely high-B tolerant plant species (Padmanabhan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among BOR genes in plants, TaBOR1.2 in wheat is reported to be induced under toxic levels of B supply (Leaungthitikanchana et al 2013), although the physiological function of TaBOR1.2 is still unclear. It has been also reported that transcript levels of a homologous gene to BOR (Bot1) is induced by high-B treatment in shoots of Puccinellia distans, an extremely high-B tolerant plant species (Padmanabhan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, BOR1 has been reported to have a similar function in other species, including OsBOR1 in rice (Nakagawa et al 2007), TaBOR1 in wheat (Leaungthitikanchana et al 2013), VvBOR1 in grape (Vitis vinifera L.) (Perez-Castro et al 2012) and CmBOR1 in Citrus macrophylla Wester. (Cañon et al 2013).…”
Section: Cloning and Characteristics Of B Transporter Genesmentioning
confidence: 97%
“…Fang60, which is classified as a B-efficient variety (Jamjod et al 1992) and Bonza, which is classified as a B-inefficient variety (Rerkasem et al 1997a) were used in this study. Three BOR1-like genes (named TaBOR1.1, TaBOR1.2 and TaBOR1.3), which is the most similar to OsBOR1 in amino acid sequence, were identified from the wheat genome, and these are functional efflux transporters of B, as was the case for AtBOR1 and OsBOR1 (Leaungthitikanchana et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the primers were shown in Table 1. The sequences of TaBOR1.1, TaBOR1.2, TaBOR1.3 is described in previous reports (Leaungthitikanchana et al 2013) The …”
Section: Rna Extraction and Quantitative Real-time Rt-pcrmentioning
confidence: 99%